Nuclear factor-I and activator protein-2 bind in a mutually exclusive way to overlapping promoter sequences and trans-activate the human growth hormone gene. - Courtois, S J (1990)
Transcription of the human growth hormone (hGH) gene and its regulation are controlled by trans-acting factors that bind to hGH gene promoter sequences. Several DNase I footprints have been described within 500 bp of this promoter, one of which (-289 to -267) has not yet been ascribed to a defined factor. By DNase I footprinting, gel mobility shift, and methylation interference assays with extracts from HeLa cells and GH-producing pituitary tumor (GC) cells, we show that this factor belongs to the NF-I family. When NF-I was competed out of the cell extracts, the trans-acting factor AP-2 bound to the same site as NF-I. AP-2 was present not only in HeLa cells, but also in GC cells albeit at a much lower concentration. Consistent with the mutually exclusive binding of NF-I and AP-2, their methylation interference patterns included four guanine residues that were crucial for binding of both NF-I and AP-2. Cell-free transcription from the hGH gene promoter showed that these two factors can transactivate this gene.